Normative Analysis of Unlawful Acts of State Administrative Officials Related to the Implementation of State Administrative Court Decisions - Ridwan Muhammad; Irham Rosyidi; Nam Rumkel (Peneliti.net, 2021)
This study aimed at determining and finding: (1) whether the unlawful act of the State Administrative Officers as a Defendant was caused by the Article formulation 116 (2) and paragraph (3) of Law Number 51 of 2009 concerning the Second Amendment of Law Number 5 of 2009 1986 concerning the State Administrative Court; and 2) the legal consequences if the defendant (TUN official) does not implement the decision of the State Administrative Decision. By using normative legal research methods which is examining secondary data or library materials that are focused on testing the application of norms in positive law; Analyzing unlawful acts committed by State Administrative Officers (Mayor of Tidore Kepulauan) because State Administrative Court Decisions State which has permanent legal force were not implemented. The results of the study indicated that (1) There was an unlawful act committed by the State Administrative Officers, in this case the Mayor of Tidore Kepulauan, which was not carried out by Ambon State Administrative Court Decision Number: 10/G/2015/PTUN.ABN on November 12, 2005. (2) There was a legal uncertainty as the decisions by the Mayor of Tidore Kepulauan were not implemented, so Ambon State Administrative Court's decision had neither been effective nor legally certain. (3) Those problems were caused by Article 116 paragraph (2) and paragraph (3) of Law Number 5 of 1986 which handed over the implementation of Ambon Administrative Court decision to the defendant (Contrarius Atus principle). (4) There was a legal uncertainty for the plaintiff. 5) Unclear guarantees of the rights of the plaintiffs